Features of the intestinal microbiota functional status in early-aged children with rotavirus infection - Vorobiova, N.; Usachova, O.; Воробйова, Наталія Володимирівна; Усачова, Олена Віталіївна (My University, 2021)
The aim is to assess the intestinal microflora functional and structural disorders in early-aged children in the dynamics of rotavirus infection by studying intestinal metabolites in faeces – short-chain fatty acids (SCFA).
Keywords: rotavirus infection; early-aged children; gut microbiota; short-chain fatty acids